Demak Sufism: Moderation of the Java Islamization in XVI Century In the Study of The Manuscript of Suluk Syeh Bari - Riyadi, Muhammad Irfan; Muzakki, Mohammad Harir; Hasanah, Nurul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
Islamization of the archipelago, especially in Java, took place peacefully in Demak period of the XV - XVI centuries. The retribution of walisanga with its sufism teachings was able to embrace Javanese mysticism in the embrace of Islam. The realization of this attitude of peace (penetration pacifique) without conflict shows that sufism has played an attitude of moderation such as appreciation, tolerance, and inclusive attitude so as to attract the sympathy of Hindu-Javanese mystics into Islam. This paper is intended to reveal how Islamic moderation occurs in Demak, for it is studied by an authentic Sufi manuscript published by Demak written by Sunan Bonang under the title Suluk Syeh Bari. This manuscript is studied using the content analysis method by prioritizing the concept of moderation. This study concludes that Suluk Syeh Bari by Sunan Bonang is the foundation for the teachings of moderate Islamic Sufism since the beginning of Islamization in Java. His moderation teachings include 1) inclusive attitudes in the spirit of divinity, 2) perfection of the soul, realizing noble, wise, and open minded. 3) Open attitude and tolerance towards others through the teachings of Sufism, Ridlo, and always happy. 4) Respect religious acculturation. This attitude will be inherited by his two students, namely Sunan Kalijaga and Syeh Siti Jenar, who gave birth to acculturative Islam (Islam of the archipelago).